Reenacting the past - Fitzsimmons Frey, Heather; Schweitzer, Marlis (My University, 2022)
This chapter explores cultural practices of reenacting the past in the present. How have understandings of reenactment, embodiment, and lived experience shaped, constrained, and misdirected interpretations of people’s actions in the present that purposefully reference the past? What is the state of this scholarship? What are the principal critiques and new directions?
Keywords: reenactment; costume; performance; embodiment; new materialism; sensory studies; authenticity; racism